Thermochemical conversion of coal and biomass blends in a top-lit updraft fixed bed reactor: Experimental assessment of the ignition front propagation velocity. (1st April 2021) - Quintero-Coronel, D.A.; Lenis-Rodas, Y.A.; Corredor, L.A.; Perreault, P.; Gonzalez-Quiroga, A.
Abstract: Co-thermochemical conversion of coal and biomass can potentially decrease the use of fossil carbon and pollutant emissions. This work presents experimental results for the so-called top-lit updraft fixed bed reactor, in which the ignition front starts at the top and propagates downward while the gas product flows upwards. The study focuses on the ignition front propagation velocity for the co-thermochemical conversion of palm kernel shell and high-volatile bituminous coal. Within the range of assessed air superficial velocities, the process occurred under gasification and near stoichiometric conditions. Under gasification conditions increasing coal particle size from 7.1 to 22 mm decreased ignition front velocity by around 26% regardless of the coal volume percentage. Furthermore, increasing coal volume percentage and decreasing coal particle size result in product gas with higher energy content. For the operation near stoichiometric conditions, increasing coal volume percentage from 10 to 30% negatively affected the ignition front velocity directly proportional to its particle size. Additional experiments confirmed a linear dependence of ignition front velocity on air superficial velocity. Further steps in the development of the top-lit updraft technology are implementing continuous solids feeding and variable cross-sectional area and optimizing coal particle size distribution. Highlights: Gasification and near stochiometric operation conditions with biomass-coal blends. Notable variability of the ignition front propagation velocity with axial position. Minor influence of coal percentage on ignition front velocity for gasification. Coal percentage decreases ignition front velocity near stochiometric conditions. Continuous feeding and adjustable throughput critical for technology development.